A fast way for matrix multiplication - Oh, Yi Hong (2018)
The importance of matrix multiplication is immense. Considerable amount of applications in computer science requires matrix multiplication. The Strassen’s algorithm for multiplying 2 × 2 matrices requires seven multiplications and eighteen additions. Winograd showed that seven multiplications are the minimal amount multiplying 2 × 2 matrices. Winograd also discovered a Strassen-like algorithm with fifteen additions together with Coppersmith. Research carried out in this field are generally done through mathematical theorems. The paper attempts to find a better Strassen-like algorithm through an exhaustive method.